Descent of Darwin : the Popularization of Darwinism in Germany, 1860-1914. - Kelly, Alfred (The University of North Carolina Press, 1981)
In Germany, more than anywhere else, Darwinism was a sensational success. Setting his analysis against the background of popular science, Kelly follows popular Darwinism as it permeated education, religion, politics, and social thought in Germany. He explains how the popularizers changed Darwin's thought in subtle ways and how these changes colored their perceptions of Darwinism. Among the first purveyors of mass culture, the Germans provide valuable clues as to how seminal ideas move through a society. Originally published in 1981.